(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Healthy living behavior in food must be implemented in society from an early age. School-age children are a critical age group because at that age a child is vulnerable to experiencing health problems that originate from unhealthy food. Apart from that, school-age children are also very sensitive to stimulation so they are easy to guide, direct and still have good habits, including healthy living habits. The aim of this service was to increase students’ knowledge about healthy food. The methods used in this community service activity are lectures, practices and games. The results showed that students and teachers were very enthusiastic and follow every step taken by the speaker regarding healthy food. After the material was finished, the students actively answered all the questions from the presenter and they enjoyed practicing together in the room because the practice used games that were easy to do for the students. In conclusion, students’ knowledge about healthy food in SB Kuala Langat, Malaysia increased after being given education. Providing education about healthy food, it is hoped that teachers and students at the SB Kuala Langat will have good and healthy habits.